Demand for CT scans increases during transition from paediatric to adult care: an observational study from 2009 to 2015 - Thurley, Peter; Crookdake, Jonathan; Norwood, Mark; Sturrock, Nigel; Fogarty, Andrew W. (British Institute of Radiology, 2017)
OBJECTIVE: Avoiding unnecessary radiation exposure is a clinical priority in children and young adults. We aimed to explore demand for CT scans in a busy general hospital with particular interest in the period of transition from paediatric to adult medical care. METHODS: We used an observational epidemiological study based in a teaching hospital. Data were obtained on numbers and rates of CT scans from 2009 to 2015. The main outcome was age-stratified rates of receiving a CT scan. RESULTS: There were a total of 262,221 CT scans. There was a large step change in the rate of CT scans over the period of transition from paediatric to adult medical care. Individuals aged 10-15 years experienced 6.7 CT scans per 1000 clinical episodes, while those aged 19-24 years experienced 19.8 CT scans per 1000 clinical episodes (p<0.001). This difference remained significant for all sensitivity analyses. CONCLUSION: There is almost a threefold increase in rates of CT scans in the two populations before and after the period of transition from paediatric to adult medical care. While we were unable to adjust for case mix or quantify radiation exposure, paediatricians' diagnostic strategies to minimize radiation exposure may have clinical relevance for adult physicians, and hence enable reductions in ionizing radiation to patients. Advances in knowledge: A large increase in rates of CT scans occurs during adolescence and paediatricians' strategies to minimize radiation exposure may enable reductions to all patients.